Meeting report: Tenth International Conference on Hantaviruses - Papa, Anna (Antiviral Res, 2016)
The 10th International Conference on Hantaviruses, organized by the International Society on Hantaviruses, was held from May 31–June 3, 2016 at Colorado State University, Fort Collins, CO, USA. These conferences have been held every three years since 1980. The current report summarizes research presented on all aspects of hantavirology: ecology and epidemiology, virus replication, phylogeny, pathogenesis, immune response, clinical studies, vaccines and therapeutics.